Uncoupling plant growth and defense through phytohormone crosstalk modification - Johnston, Grace Allen, author; Argueso, Cris, advisor; Leach, Jan, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2023)
Phytohormones are essential regulators of development and response to biotic and abiotic stresses. Activation of the plant immune system by pathogen attack often results in changes in plant growth, frequently leading to smaller plants with reduced seed set. Previously, we discovered that cytokinin (CK), a hormone known for its role in the regulation of cell division and plant growth, also has an important role in the activation of defense against pathogens through a synergistic interaction with the defense hormone salicylic acid (SA). Here, we address whether these two phytohormones also regulate the negative effect of immune activation on plant growth. Differential gene expression analysis and physiological assays were used to characterize the crosstalk between CK and SA in growth and defense in Arabidopsis thaliana plants with altered states of immunity. We show that the interplay between the phytohormones CK and SA regulates both defense responses to pathogens and plant development. Endogenous levels of these two hormones were modulated in the snc1 ckx3 ckx5 (s35) triple mutant. The three mutations result in increased CK and SA content simultaneously and yields a novel reproductive growth phenotype. When challenged with pathogens from diverse lifestyles, the s35 mutant conserves an autoimmune phenotype. Transcriptome analysis of s35 reproductive tissue reveals differential regulation of genes associated with nitrogen response and regulation of redox status. Our data suggests that the increased content of both CK and SA hormones contributes to a rebalancing of redox homeostasis and perception of nutrient availability within the shoot apical meristem (SAM), resulting in the uncoupling of reproductive growth and pathogen defense. Further experimentation and investigation into the mechanistic interactions mediating the balance between plant growth and defense could lead to implementation of phytohormone crosstalk engineering to target specific advancements in crop species.
Keywords: cytokinin; phytohormone crosstalk; Arabidopsis thaliana; salicylic acid; growth defense tradeoff